Peningkatan Literasi Dasar Siswa Sekolah Dasar melalui Kegiatan Membaca Bersama di SDN Inpres Skow Mabo Jayapura - Septikasari, Dian; Warikar, Amelia (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
This community service programme aims to strengthen basic literacy skills among primary school students at SDN Inpres Skow Mabo, a border-area school facing limited literacy resources and low student reading interest. The activity was initiated to respond to the school’s need for engaging and contextual literacy strategies that support the School Literacy Movement. The programme employed a participatory and collaborative approach involving lecturers, teachers, and students through three main stages: preparation, implementation, and evaluation. Key activities included shared reading sessions, teacher training on interactive reading techniques, and creative literacy activities such as storytelling, poetry reading, and short story writing. Evaluation was conducted through observations, interviews, and assessments of students’ retelling abilities. The results show significant improvements in students’ reading comprehension, confidence, and interest in reading, alongside strengthened teacher capacity in integrating literacy strategies into classroom learning. The establishment of reading corners and locally themed reading materials also contributed to developing a sustainable literacy culture. This programme highlights the importance of collaborative, contextual, and practice-based approaches in enhancing literacy skills in remote primary schools.